The politics of crackdowns on Africa’s informal vendors - Resnick, Danielle (Comparative Politics CUNY, 2019)
Crackdowns on informal vendors are a common form of violence against the poor in many cities in developing countries. This article uses a media events database to examine crackdowns of informal vendors in Accra, Dakar, and Lusaka from 2000 to 2016. During this period, Accra demonstrated consistently high levels of violence towards vendors, while violence increased in Dakar and decreased in Lusaka. The article argues that these trends are driven by differences in political decentralization for municipal authorities, variations in their administrative mandates over vending, and the degree of influence vendors hold as an electoral constituency. Through a structured comparison of the governance of informal vendors across multiple cities, the article demonstrates how state violence manifests through everyday battles over access to public space.